2024
DOI: 10.1002/adma.202309360
|View full text |Cite
|
Sign up to set email alerts
|

Salt‐Assisted Vapor–Liquid–Solid Growth of 1D van der Waals Materials

Thang Pham,
Kate Reidy,
Joachim D. Thomsen
et al.

Abstract: We introduce the method of salt‐assisted vapor‐liquid‐solid (VLS) growth to synthesize one‐dimensional (1D) nanostructures of trichalcogenide van der Waals (vdW) materials, exemplified by niobium trisulfide (NbS3). The method uses a unique catalyst consisting of an alloy of Au and an alkali metal halide (NaCl) to enable rapid and directional growth. We demonstrate high yields of two types of NbS3 1D nanostructures, nanowires and nanoribbons, each with sub‐ten nanometer diameter, tens of micrometers length, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…The case of the Sn(Br/I)P crystals suggests that the propagation of crystallographic screw axes along the long-axis of weakly bound chains leads to helical structures. ,,, Encouragingly, the immense interest in exfoliable 1D crystals has sparked the search for classes of inorganic crystals with sub-nanometer-thick chains held by vdW interactions. Thus, the identification of screw axis symmetry within emergent 1D vdW crystal classes led to our discovery of helical motifs in III–VI–VII 1D vdW crystals (III = Al, Ga, In; VI = S, Se, Te; VII = Cl, Br, I). ,,,, We found that crystals in this class manifest tetrahelical motifs along chains held by vdW interactions. ,,, For example, InSeI is a semiconductor consisting of periodic helical chains defined by a 4 1 screw axis and shows highly temperature-sensitive bandgaps in the visible range (Figure S1). ,,, Substitution of Ga atoms to the In site led to GaSeI, which is the first freestanding inorganic tetrahelix that is an approximate Boerdjik–Coxeter (B–C) helix .…”
mentioning
confidence: 99%
“…The case of the Sn(Br/I)P crystals suggests that the propagation of crystallographic screw axes along the long-axis of weakly bound chains leads to helical structures. ,,, Encouragingly, the immense interest in exfoliable 1D crystals has sparked the search for classes of inorganic crystals with sub-nanometer-thick chains held by vdW interactions. Thus, the identification of screw axis symmetry within emergent 1D vdW crystal classes led to our discovery of helical motifs in III–VI–VII 1D vdW crystals (III = Al, Ga, In; VI = S, Se, Te; VII = Cl, Br, I). ,,,, We found that crystals in this class manifest tetrahelical motifs along chains held by vdW interactions. ,,, For example, InSeI is a semiconductor consisting of periodic helical chains defined by a 4 1 screw axis and shows highly temperature-sensitive bandgaps in the visible range (Figure S1). ,,, Substitution of Ga atoms to the In site led to GaSeI, which is the first freestanding inorganic tetrahelix that is an approximate Boerdjik–Coxeter (B–C) helix .…”
mentioning
confidence: 99%